2005
DOI: 10.1159/000082128
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status of Neonates Exposed in utero to Tobacco Smoke

Abstract: To investigate the influence of maternal smoke exposure on neonatal and maternal antioxidant status, 39 mothers who were active smokers, 14 mothers exposed to environmental tobacco smoke (ETS), 17 controls, and their newborns were included in a prospective, controlled study. Plasma total antioxidant capacity, measured as total radical-trapping antioxidant parameter (TRAP) and ferric reducing antioxidant power (FRAP), and concentrations of specific antioxidants were measured in cord and in maternal blood. A sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 68 publications
6
28
1
1
Order By: Relevance
“…Our data showed that the extent of maternal exposure to environmental tobacco had a significant effect on maternal, but not neonatal, serum vitamin A concentration, which is consistent with previous reports (31,32). The different effect of environmental tobacco smoke on maternal and neonate vitamin A status was probably related to the efficient buffering function of the placenta.…”
Section: Relationship Between Maternal and Cord Vitamins A E And Csupporting
confidence: 92%
“…Our data showed that the extent of maternal exposure to environmental tobacco had a significant effect on maternal, but not neonatal, serum vitamin A concentration, which is consistent with previous reports (31,32). The different effect of environmental tobacco smoke on maternal and neonate vitamin A status was probably related to the efficient buffering function of the placenta.…”
Section: Relationship Between Maternal and Cord Vitamins A E And Csupporting
confidence: 92%
“…Recent reports demonstrated an increase in haemeoxygenase 1 and 2 expressions in the placenta of smoking mothers, and increased levels of ceruloplasmin in the plasma of newborns and mothers exposed to tobacco smoking. 16,17 These molecules are known as antioxidants that might reduce oxidative stress in the ischemic retina of premature infants, which might inhibit the excessive expression of angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Animal research demonstrates that environmental, or passive smoke exposure, affects fetal brain development in the same manner as exposure through direct maternal routes [23]. In humans, second hand smoke exposure during pregnancy results in the same degree of negative pregnancy outcomes as direct maternal use, including genotoxic effects [24], decreased fertility [25], neonatal antioxidant status [26], and increased fetal mortality, preterm births, and reduced fetal growth [27,28,29]. Given that nicotine exposure affects neural development at doses lower than those required to affect physical growth, the finding that birth weight and other physical correlates of nicotine exposure are impacted in fetuses whose mothers were passively exposed to smoke suggests that CNS correlates are likely to be implicated.…”
Section: Introductionmentioning
confidence: 99%